MEDICATION SAFETY PROFILE: A CASE REPORT OF FIRST TRIMESTER PREGNANCY PATIENTS WITH DEEP VEIN THROMBOSIS DIAGNOSIS ACCOMPANIED BY COMORBIDITY - Aritonang, Anggi Chatie Yunida; Rambe, Rima Elfitra; Henny Sri Wahyuni; Lumbanraja, Sarma Nursani (Talenta Publisher, 2025)
Pregnancy is a hypercoagulable state that elevates the risk of Deep Vein Thrombosis (DVT). The selection of pharmacological interventions for DVT during pregnancy necessitates rigorous consideration of both maternal and fetal safety. Management becomes increasingly complex when the condition is accompanied by comorbidities, which often lead to polypharmacy and a higher potential for drug-drug interactions. This case report discusses a 33-year-old pregnant woman in her first trimester diagnosed with DVT in the left lower extremity, complicated by secondary hypertension, type 2 diabetes mellitus, and fever. The therapeutic regimen comprised 13 medications, including anticoagulants, antibiotics, analgesic-antipyretics, antiemetics, antihypertensives, and antidiabetic agents. Medication safety profiles were evaluated based on FDA pregnancy categories and other peer-reviewed references. Potential drug interactions were analyzed using the UpToDate® Lexicomp™ database. The study identified two drugs in category A, five in categories B and C, respectively, and one agent for which data was unavailable. Four potential drug interactions were identified, ranging from moderate to minor severity. All prescribed drugs demonstrated an adequate safety profile supported by current clinical literature. This study emphasizes the critical importance of a thorough risk-benefit analysis. Stringent monitoring is essential to ensure both the safety and efficacy of the treatment.